The Influence of Financial Performance, Capital Structure, Intellectual Capital on Company Value - Farhatulmaula, Dwi Suci; Suparmin (Formosa Journal of Sustainable Research, 2024)
The purpose of this research is to determine the influence of Financial Performance, Capital Structure, Intellectual Capital on Company Value. This study uses a quantitative approach. The population of this research is Consumer NonCyclical Companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the 2018-2022 period. This research consisted of 85 samples from 17 companies and the samples were determined using the purposive sampling method. This research uses panel data regression techniques which are processed using E-Views 10. The results of the research show that Financial Performance, Capital Structure, Intellectual Capital simultaneously influence company value. Financial Performance has a significant effect on company value, Capital Structure and Intellectual Capital have no partial effect on Company Value